Pembinaan Usaha Kreatif Melalui Pemanfaatan SDM dan SDA dalam Bermu’amalah - Nurhayati Zein; Wardani Purnama Sari; Kasmiati; Irawati (Tasnim Journal for Community Service, 2020)
This dedication is motivated by the lack of guidance from the government and competent people to foster communities living in housing, lack of public / unproductive knowledge in processing natural resources in their area, relatively limited business opportunities, limited knowledge of housewives in utilizing natural resources, and people feel insecure and do not have the funds to do business. Seeing these problems, this dedication aims to empower housewives through the use of HR and SDA in Bermu'amalah. In order to achieve this, the service provider uses the ABCD method which is a community development concept based on local assets found in an area. The results of the service went well and smoothly and the community, especially mothers, young women and children, were enthusiastic and felt helped to get useful knowledge.